2006
DOI: 10.1021/ol062238j
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative Oligothiophenes Based on a Hexafluorocyclopentene-Annelated Thiophene Unit

Abstract: [Structure: see text] The synthesis of hexafluorocyclopenta[c]thiophene and its based oligothiophenes is described. The effectiveness of a hexafluorocyclopentene unit to lower the LUMO level without disturbing the effective conjugation could be unambiguously clarified by spectroscopic measurements and X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Synthesis of CPT was reported from Mac Dowell et al in 1966 . Pioneer work regarding the synthesis of different CPT and their application in OFETs has been reported later by Y. Aso et al . and Zade et al .…”
Section: Introductionmentioning
confidence: 96%
“…Synthesis of CPT was reported from Mac Dowell et al in 1966 . Pioneer work regarding the synthesis of different CPT and their application in OFETs has been reported later by Y. Aso et al . and Zade et al .…”
Section: Introductionmentioning
confidence: 96%
“…We previously reported that the hexafluorocyclopenta[c]thiophene (F) 14 repeated oligothiophenes (F 2 , F 4 and F 6 ) ( Figure 1a) clearly showed a positive shift of the electrochemical reduction potential and red shift of the absorption maximum as the number of the F units increased. 15 These results clearly indicate that the annelation of hexafluorocyclopentene at the thiophene rings contributes to an increase in the electron-accepting nature of π-conjugated systems without disrupting the effective conjugation.…”
Section: Introductionmentioning
confidence: 97%
“…Significant progress has recently been made in the development of p‐type OFET materials 2. However, limited studies have been conducted on the development of n‐type OFET materials 3–14. This is because of the insufficiency of their molecular design in stabilizing electron‐injected species and arranging the molecular ordering for efficient electron transport in the solid state.…”
Section: Introductionmentioning
confidence: 99%